Kroger Disposable Plastic Shopping Bag - Science History Institute (2023)
A gray plastic shopping bag with red print. This bag, manufactured for Kroger supermarkets, has a #2 HDPE recycling indication, meaning it is made from high-density polyethylene plastic and can be recycled. Information about returning the bag to Kroger as part of a recycling program is written on the bottom of the bag. The polyethylene polymer that makes up this plastic bag was synthesized from fossil fuels such as crude oil or natural gas obtained via fracking. When disposed of, the first half-life, or the time in which the material loses 50% of its original mass, is approximately 250 years in a landfill or soil environment.
Keywords: Plastics; Plastic bags; Plastics industry and trade; Plastics--Environmental aspects; Kroger Company; Recycling (Waste, etc.); High-density polyethylene